A comparison of two approaches for incorporating air voids in asphalt pavement oxidation modeling with a multiyear, multisite set of field core data. (1st February 2016) - Rose, Avery A.; Cui, Yuanchen; Glover, Charles J.
ABSTRACT: Pavement oxidation modeling has been used to predict pavement aging, or more specifically, oxidation and hardening. Two approaches for incorporating pavement air voids in the modeling analysis have been developed—the cylindrical approach and the diffusion depth (dD ) approach. The work reported herein compares these approaches with a multiyear, multisite set of field data. The dD approach produces field calibration factor values that are closer to theory, and is better able to predict aging variation with pavement depth. Results suggest the presence of undetected smaller air voids, in agreement with previous work.